THE USAGE OF YOUTUBE VIDEO IN TEACHING ENGLISH FOR YOUNG LEARNER (TEYL) FOR SIXTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT - Nurna ningsih; Arin Arianti (The Center for Language Development, Mataram State Islamic University., 2019)
The objective of the research is to know the student’s mastery in using YouTube as teaching media while the students learn to be a peer teacher in TEYL. TEYL is Teaching English for Young Learner is one of the subjects that is taught for sixth semester students of English Department in Veteran Bangun Nusantara University of Sukoharjo. Students learnt to teach their friends as if their friends were young learner students by using many kinds of teaching Medias. Youtube video is the most favorite teaching media because it is easy to get by downloading it or just see it. Qualitative method was used in the study. The subject of the study was 6th semester students of English Department. The collecting data of the study were used observation, interview, and documentation. The observation was used in order to know students’ teaching mastery about YouTube as a teaching media. The interview used to know the students feel, inspiration of using YouTube, and the application of YouTube in class. The documentation itself were divided into three. First was video recording, second was note taking and third was pictures. While the data of the research was the script based on the video recording. Based on the research, the students used YouTube as teaching media with different treatment. 1. Collecting some videos in a PowerPoint the way to serve it to the other students, 2. YouTube video was combined with some written explanation in a PowerPoint, 3. the other students only used a video then played it as a teaching medium, 4. Students downloaded songs video from YouTube but it does not play in class but the students use the song by changing the lyric. Then the students sang it with the variation lyric they already made.